Загальні засади утримання інноваційно-інвестиційного портфеля в зоні його ефективності - Васильцова, С.О. (Економіка промисловості, 2012)
Определено, что портфель инновационных проектов выступает высокотурбулентной средой. В подавляющем большинстве случаев повлиять на рыночные, общественные и другие события, которые изменяют перспективу проектов, портфелю не удается. Однако остается та часть, на которую повлиять удается, и своевременное отслеживание изменений перспектив проекта портфелю позволит выполнять соответствующие изменения его структуры меньшей ценой.
Ключевые слова: портфель проектов, коммерциализация, инновации, принципы, ценность инноваций. Визначено, що портфель інноваційних проектів виступає високотурбулентним середовищем. У переважній більшості випадків вплинути на ринкові, суспільні та інші події, що змінюють перспективу проектів портфеля, не вдається. Проте залишається та частина, на яку вплинути вдається, та своєчасне відстеження змін перспектив проекту портфеля дозволить виконувати відповідні зміни його структури меншою ціною.
Ключові слова: портфель проектів, комерціалізація, інновації, принципи, цінність інновацій. Strategy of the company is aimed very often at breacking growth, creation and capture of markets. To implement such ambitious tasks, the business forms a portfolio of projects. The project office created simultaneously has a fundamental task: to maintain the implementation of the portfolio of real investment-innovative projects (PRIIP) in the actual state, to provide a successive realization of projects and inflows of profits which may come from realization of innovative products.
The aim of the work is to improve the principles which allow maintaining the innovative-investment portfolio in the area of its efficiency. After formation of PRIIP and beginning of the work on the projects, their efficiency is provided due to everyday job to maintain it in the effective area.
It is obvious that the portfolio of innovative projects is a highly turbulent environment. In the majority of cases, it is impossible to influence the market, public and other events which change the prospects for the projects. However, there is a part of projects that fall under influence; the timely watching of changes in prospects for projects portfolio allows to make proper changes in structure of the portfolio (or project) at a less price. The increase of efficiency of PRIIP management is achieved by different measures of technical, organizational and administrative character. One of the most actual terms of providing the effective management is the introduction and subsequent observance of corporate principles of management.
Keywords: portfolio of projects, commercializa-tion, innovations, principles, value of innovations.